Smartphone-based indoor localization by fusion of acoustic ranging and PDR - Mao PANG; Mei WANG; Xiyu SONG; Liyan LUO; Kun RUAN (物联网学报)
A novel indoor localization algorithm that integrates acoustic ranging and pedestrian dead reckoning (PDR) algorithm was presented,to reduce the accumulated error of the inertial sensors in the process of indoor positioning using PDR.Firstly,the PDR was used for position estimation.Then,the distance between the mobile phone and the wall was measured by using sound waves,and the cumulative error in the PDR was corrected by combining the above position and the distance with the known indoor map information.Hence,long-term stable indoor positioning can be achieved without laying out any nodes.In order to solve the problem that the echo signals reflected by the wall under long-distance conditions were difficult to detect,signal enhancement on the echoes reflected from the target wall was performed by using beamforming,taking advantage of the characteristics of the built-in dual microphones in the smartphone,then the effective measurement distance was increased and the application range of the proposed method was expanded.Experimental results show that the average positioning error of the proposed fusion localization method is 0.427 m.Compared with the results of using PDR alone,the average positioning error is reduced by 2.748 m.